PURIFICATION AND CHARACTERIZATION OF SALIVARY AMYLASE INHIBITOR EXTRACTED FROM BARLEY - & Hakeem, Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Amylase inhibitors were purified by many sequential steps included concentration by gradual addition of ammonium sulfate at  saturation ratios. ranged from 0 to 90% . The best ratio of saturation was found to be 70% as the specific activity and inhibition activity toward Human alpha-amylase(HAS)  were the highest ( 8 U/mg and 6 U/ml respectively as compared to those of the rest ratios, the ratio of saturation with ammonium sulfate 60 % and then 50%, (5.8 ,5.5  )U/ml and( 7.7 ،7 )U/mg respectively for inhibition activity and specific activity and for  40% ,30%20%  saturation  the inhibition activity and specific activity were(5 ،4.8 ،4 ) u/ml (6.6 ،6 ،5.8) u/mg respectively .The precepitation step was followed by ionic exchange chromatography technique by DEAE-cellulose column( 3×11 )cm and the results showed that there was one peak with inhibition activity toward (HAS). Further  purification steps were conducted using gel filtration on Sephacryl S-200 column    (1.5  ×  60)cm; the purification folds was5.59 times with outcome of 46.5%.The results of alpha-amylase inhibitors characterization showed that the molecular weight was about 23.44 and 22.9  kDa  as determined by electrophoresis and gel filteration respectively.